2004
DOI: 10.1124/jpet.103.063362
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for the Inhibition of Genital Vascular Responses by Antidepressants in a Female Rabbit Model

Abstract: Vaginal and clitoral vasodilator responses (genital vascular responses; GVRs) to pelvic nerve electrical stimulation in female rabbits were measured by laser Doppler flow needle probes. The intravenous administration of various treatments was evaluated. GVRs were attenuated by a nitric-oxide synthase inhibitor (48.5 and 51.8% of control at 8 Hz in the vagina and clitoris, respectively) and norepinephrine (NE) (78.5 and 61.5%), whereas serotonin (5-HT) had no inhibitory effect. The selective 5-HT reuptake inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…215 Fluoxetine, 216 -220 clomipramine, 220 paroxetine, 218 and citalopram 218 have inhibited apoptosis in neoplastic models. Duloxetine inhibits nitric oxide synthase 237 and, hence, free radical generation. 221 Selective NERIs block free radical generation including intramitochondrial radicals, mitochondrial permeability transition pore development, and several types of apoptosis in various cell lines.…”
Section: Modafinilmentioning
confidence: 99%
“…215 Fluoxetine, 216 -220 clomipramine, 220 paroxetine, 218 and citalopram 218 have inhibited apoptosis in neoplastic models. Duloxetine inhibits nitric oxide synthase 237 and, hence, free radical generation. 221 Selective NERIs block free radical generation including intramitochondrial radicals, mitochondrial permeability transition pore development, and several types of apoptosis in various cell lines.…”
Section: Modafinilmentioning
confidence: 99%
“…However, in a previous study, we demonstrated that the effects of these molecules on GVR in female rabbits are not related to the inhibition of serotonin reuptake [7]. Based on the specific effects of the NOS substrate, l ‐arginine, and the α‐blocker, phentolamine, we reported that paroxetine exerted its inhibitory effect on GVR by reducing NO production, and venlafaxine‐induced inhibition of GVR in female rabbits was due to its ability to increase norepinephrine availability, whereas both reduction of NO generation and potentiation of adrenergic system are contributing to the inhibitory action of duloxetine [7]. In addition to these acute effects, more prolonged administration of these type of antidepressants has been shown to interfere with NO and adrenergic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the mechanisms responsible for the inhibition of GVR induced by the antidepressants depend on the specific molecule administered. Disruption of the nitric oxide (NO) pathway would be responsible for the inhibitory effect of paroxetine and, partially, for that of duloxetine, whereas the increase in adrenergic input would cause the inhibitory effects of venlafaxine and, partially, those of duloxetine [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…235,236 SNRIs like duloxetine inhibit GSK-3␤, nitric oxide synthase, mitochondrial permeability transition pore opening, and several types of apoptosis in various cell lines. Duloxetine inhibits nitric oxide synthase 237 and, hence, free radical generation. The SNRI nortriptyline blocked glutamate-induced mitochondrial permeability transition pore opening and apoptosis in a transgenic mouse Huntington's disease model.…”
Section: Methodsmentioning
confidence: 99%